THE EFFICACY OF LEARNING COMMUNITY IN LEARNING ENGLISH SPEAKING SKILL - M. Bambang Purwanto; Despita (Universitas Islam Ogan Komering Ilir Kayuagung, 2022)
At Junior High School 4 Sungai Lilin, there is a learning community for developing English speaking skills. Learning communities are one strategy that can be used to help students improve their ability to speak (community learning and studying together). Learning community is a notion for fostering shared learning in the classroom, the learning process between teachers and students, students with other students, and even between the school community and the community outside of the school. This study sought to characterize the degree to which the learning community's effectiveness in helping high school students in class IX at Junior High School 4 Sungai Lilin learn English at its height, as determined by experimental design research employing a pretest-posttest control group. Additionally, data were gathered by observation, and both descriptive and inferential statistics were used to assess oral tests. The findings demonstrated that the learning community is useful in raising the English proficiency of class IX junior high school students at Sungai Lilin. It is based on data analysis that revealed that students who take classes that integrate learning in the learning community have an average test speaking competence that is greater than that of students who take classes where such integration is not a part of the learning community